Hubungan Pengetahuan Tentang Triase DenganTingkat Kecemasan Pasien Label KuningDi Instalasi Gawat DaruratRumah Sakit Dr. Moewardi Surakarta - Budiaji, Wahyu, Arief Wahyudi Jadmiko, S.Kep., Ns., M.Kep (2016)
Emergency Room (ER) is one unit of hospital services that provide first aid and as the first entry of patients with emergency conditions. The number of patients in emergency department visits made nurses have to sort patients by severe level or so-called triage. Triage classification most commonly used colors: red, yellow, green and black. The yellow color shows the high priority that the victim moderet emergent and medical treatment it can be delayed in less than 30 minutes. The number of patients who come in the ER from a variety of socio-economic background of education and experience as well as ignorance of the management of triage in the ER create the perception of different patients coupled with the ER condition that overcrowded will add inconvenience and also increase the level of patient anxiety. This study aims to determine the relationship of the level of knowledge about the patient's anxiety level triage with a yellow label in ER Hospital Dr. Moewardi Surakarta. This research was a descriptive correlative with cross sectional approach. The study population was the number of patient visits triage with a yellow label in ER Hospital Dr. Moewardi. A sample of 95 patients with accidental sampling technique. Collecting data using questionnaires were analyzed using Spearman rank correlation test. Spearman rank correlation test results the correlation between knowledge of triage with yellow label patient anxiety levels in ER Hospital Dr. Moewardi Surakarta acquired value Spearman rank correlation (rs) was -0.260 (p-value = 0.011), so the decision was a test of H0 rejected. The research conclusion there is a relationship with the level of knowledge about the anxiety level of triage yellow label at the Hospital ER Dr. Moewardi Surakarta.